2022
DOI: 10.1038/s41598-022-05704-y
|View full text |Cite
|
Sign up to set email alerts
|

The sodium–glucose cotransporter 2 inhibitor ipragliflozin improves liver function and insulin resistance in Japanese patients with type 2 diabetes

Abstract: Sodium–glucose cotransporter 2 inhibitor (SGLT2i) treatment is a therapeutic approach for type 2 diabetes mellitus (T2DM). Some reports have shown that SGLT2i treatment improves insulin resistance; however, few studies have evaluated insulin resistance by the glucose clamp method. Hepatic insulin clearance (HIC) is a new pathophysiological mechanism of T2DM. The effect of SGLT2i treatment on hepatic insulin clearance and insulin resistance is not well known. We investigated the effect of SGLT2i treatment on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, the decrease in these levels observed in the metformin group may have been caused by vitamin B12 deficiency because of metformin. Finally, a previous study reported that SGLT2 inhibitors improved liver function, decreased hepatic insulin resistance, and increased hepatic insulin clearance 50 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the decrease in these levels observed in the metformin group may have been caused by vitamin B12 deficiency because of metformin. Finally, a previous study reported that SGLT2 inhibitors improved liver function, decreased hepatic insulin resistance, and increased hepatic insulin clearance 50 …”
Section: Discussionmentioning
confidence: 86%
“…Finally, a previous study reported that SGLT2 inhibitors improved liver function, decreased hepatic insulin resistance, and increased hepatic insulin clearance. 50 This is the first study that identified metabolites in serum sam- This study has several limitations. First, unfortunately, we…”
Section: Log2mentioning
confidence: 99%
“…Ipragliflozin treatment has been reported to improve liver function. 16 In the metformin group, responders had high HbA1c levels at baseline and the high fasting blood glucose levels decreased after 24 weeks. Therefore, metformin is more suitable for patients with worse blood glucose control.…”
Section: Discussionmentioning
confidence: 94%
“…GPT levels decreased in the ipragliflozin group, which may reflect the amelioration of fatty liver disease. Ipragliflozin treatment has been reported to improve liver function 16 . In the metformin group, responders had high HbA1c levels at baseline and the high fasting blood glucose levels decreased after 24 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Despite these limitations, we consider that our study would contribute to our daily clinical work or clinical studies. We previously reported that SGLT2 inhibitor increased postprandial HIC, and decreased hyperinsulinemia, insulin resistance, and liver functions [ 28 ]. We consider that our findings contribute to the treatment strategy, because we can estimate postprandial HIC from only one fasting blood sample based on our results.…”
Section: Discussionmentioning
confidence: 99%